Histological Characterization of Embryogenic and Non-embryogenic Calli of Jatropha Curcas L. - Anjani,; Shukla, Arvind; Shukla, Alok; Guru, S. K. (Indian Forester, 2013)
Two types of callus proliferation namely, embryogenic (E) and non-embryogenic (NE) calli were obtained by culturing 2 to 3 days old leaf of Jatropha curcas L. (Pant Jatropha Selection-II) in modified MS medium supplemented with 2 ppm 2,4-D, and 0.5 ppm BAP. Scanning electron micrographs indicated distinct morphology of cell shape. NE cell shape was tubular and loosely arranged cells. Embryogenic callus comprised nodular or knobby, quite deep embedded and tightly packed cell mass. Histological observations of callus sections revealed that E callus occurred on the surface as well as in the deeper regions of the callus. The abundance of vessel tracts in the callus was consistent with high content of vessel elements, rounded and cytoplasmically dense cells with totipotency. This may imply that nutrients are easily transported via these vessel tracts for the nourishment of growing somatic embryos or leafy structure. The number of vessel elements appeared to be a crucial factor in determining the E and NE calli development.